Penggunaan Clickbait Headline pada Portal Berita Tribunnews.com - Intan Nurindar Wardani; Ningsih, Masnia; Zusyana Dewi, Ratnaningrum (PAWITRA KOMUNIKA : Jurnal Komunikasi dan Sosial Humaniora, 2021)
This research examines the use of clickbait headlines on the Tribunnews news portal. .com. The problem that is the focus of this research is the use of clickbait headlines on the Tribunnews.com news portal. The method used in this research is a qualitative method descriptive research type. This study uses the Tribunnews.com object. This research uses social responsibility theory, and differentiation strategies. This research is a descriptive qualitative research using data collection techniques, namely observation, in-depth interviews, and documentation. Meanwhile, the analysis technique used is reduction, data presentation, and conclusion drawing. The results of the discussion show that the public is still aware that the clickbait carried out by Tribunnews.com can bring disappointment after reading it and a sense of dissatisfaction arises. However, many people also end up clicking again on the news headline of Tribunnews.com and visiting the website because they are tempted by booming news headlines. This evidence is strengthened, although many people feel dissatisfied, Tribunnews.com is one of the major online media in Indonesia that is able to rank 3 in Indonesia. That is because Tribunnews.com has a differentiation strategy that is clickbait in increasing viewers in the midst of competition for many online media today. As a sense of social responsibility, Tribunnews.com invites netizens who feel cheated by the news to provide comments containing suggestions for building Tribunnews.com so that in the future it will be better in broadcasting news.